FEATURES OF TRANSLITERATION OF TOPONYMS OF MACRO-CITIES IN UZBEK LANGUAGE INTO ENGLISH - Saidhoshimova Tutiyo Abulfayz kizi (International Engineering Journal For Research & Development, 2023)
Geographical names that reflect the natural conditions of a certain region, its history, changes in society, and the uniqueness of the spiritual and material wealth of the people make up the layer of toponyms in the language. Therefore, collecting information about toponyms and presenting this information in the form of various dictionaries is of practical importance not only for lexicography but also for the sciences of geography, history and cultural studies.